Pharmaceutical Botany. Manual for the Unified State Qualification Examination (USQE), Stage 1. the ―Krok-1‖ Integrated Test-Based Exam and the English Language Proficiency Test Preparation for the Second and Third-Year Students of the Pharmaceutical Faculties, Specialty 226 ―Pharmacy, Industrial Pharmacy‖, Specialization ―Technology of Perfumes and Cosmetics‖. Part I - Корнієвський, Юрій Іванович; Корнієвська, Валентина Григорівна; Куліченко, Алла Костянтинівна; Панченко, Світлана Валеріївна; Мазулін, Георгій Владиленович; Korniievskyi, Yu. I.; Korniievska, V. H.; Kulichenko, A. K.; Panchenko, S. V.; Mazulin, H. V. (Запорізький державний медичний університет, 2021)
The manual aims to prepare pharmaceutical students for the Unified State Qualification Examination (USQE), Stage 1 that consists of the following parts: the ―Krok-1‖ Integrated Test-Based Exam and the English Language Proficiency Test.